THE COMMITMENT BHISMA’S IN ORDER POLITENESS - - Hardiyanto (JURNAL IKADBUDI, 2013)
The Bhisma is a puppet character who remained faithful to uphold their oath spoken. That, of course, can reflect to its executive officers, legislative, and judicial branches of the organizers of the state in Indonesia. With that reflection, the organizers must hold fast to the vows that have been spoken before assuming his job. Remain faithful to uphold the words of the oath or affirmation is a hallmark of the Javanese community. This value is as a reflection of ethnic identity in question to hold, because the value is regarded by Javanese contain values that can reconcile the communities, especially communities that have multiculturalism. A plural society we need to keep his peace, if the mutual interaction uphold their oath spoken. Those values are potential local knowledge needed to be conserved, and its conservation through learning in school. Keywords: value of politeness in politics to the characters Bhisma’s